Digging into the digital divide: Workers' exposure to digitalization and its consequences for individual employment - Sabrina Genz; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2021)
While numerous studies have analyzed the aggregate employment effects of digital technologies, this paper focuses on the employment development of individual workers exposed to digitalization. We use a unique linked employer-employee data set for Germany and a direct measure of the first-time introduction of cutting-edge digitalization technologies in establishments between 2011 and 2016. Applying a matching approach, we compare workers in establishments investing in digital technologies with similar employees in establishments that do not make such an investment. We find that the employment stability of incumbent workers is lower in investing than non-investing establishments, but most displaced workers easily find jobs in other firms, and differences in days in unemployment are small. We also document substantial heterogeneities in the employment effects across skill groups, occupational tasks performed, and gender. Employment reactions to digitalization are most pronounced for both low- and high-skilled workers, for workers with non-routine tasks, and for female workers. Our results underline the importance of tackling the impending digital divide among different groups of workers. – – Während viele Studien die aggregierten Beschäftigungseffekte digitaler Technologien analysiert haben, konzentriert sich die vorliegende Untersuchung auf die Beschäftigungsentwicklung von individuellen Beschäftigten, die der Digitalisierung ausgesetzt sind. Wir nutzen einzigartige verbundene Arbeitgeber-Arbeitnehmer-Daten für Deutschland und ein direktes Maß der erstmaligen Einführung von modernen digitalen (4.0-)Technologien in Betrieben zwischen 2011 und 2016. Unter Verwendung eines Matching-Ansatzes vergleichen wir Beschäftigte in Betrieben, die in digitale Technologien investieren, mit möglichst ähnlichen Beschäftigten in nicht-investierenden Betrieben. Es zeigt sich, dass die Beschäftigungsstabilität von Mitarbeiterinnen und Mitarbeitern in investierenden Betrieben geringer ausfällt als in nicht-investierenden Betrieben. Allerdings finden entlassene Beschäftigte meist leicht Jobs in anderen Firmen, und es gibt nur geringe Unterschiede bezüglich der Arbeitslosigkeitstage. Die Beschäftigungseffekte variieren stark nach Qualifikation, Tätigkeit und Geschlecht. Sie sind am stärksten ausgeprägt für Geringund Hochqualifizierte, für Beschäftigte mit Nicht-Routinetätigkeiten und für Frauen. Unsere Ergebnisse unterstreichen, dass der digitale Graben zwischen Beschäftigtengruppen politisch angegangen werden sollte.
Keywords: J21; J63; O33; 330; digitalization; employment; separations; skills; tasks